ANALISIS EKSPERIMENTAL PENGARUH BELOKAN TAJAM DAN SUSUNAN PIPA TERHADAP PERPINDAHAN PANAS PADA SOLAR WATER HEATER - Nasution, Muhammad Syukri; Syuhada, Ahmad; Razali, Razali (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Hot water is water that has a temperature above the human body's temperature, which ranges between 37-100°C. The demand for hot water keeps increasing, especially for bathing purposes, as bathing with hot water is more comfortable and can help relax the body. Typically, hot water is obtained by boiling water using oil or wood-burning stoves and using electric water heaters, which increase household expenses. The best alternative to address this issue is to create a solar water heater. To improve the performance of a solar water heater, many researchers have conducted studies on this topic, but further improvements are still needed to achieve more optimal results. This research is conducted to test the effect of the number of sharp bends, the length of the pipe between sharp bends, and the arrangement of the pipe layout on the heat transfer that occurs in a 30 L solar water heater pipe with collector dimensions of 2.5 x 0.8 m². The variations made on the heating pipe involve varying the length of the pipe between sharp bends into three variations, namely (230, 670, 95) cm, arranged horizontally and vertically. Based on the research with an average solar radiation intensity of 790-850 W/m², the most optimal collector occurred in the variation III pipe (95 cm) with an end water temperature of 76.56°C, useful energy of 360.4333 W, solar water heater efficiency of 23.4714%, and convective heat transfer coefficient of 150.7833 W/m²K.